“Speaking of sexuality”: Enhancing comfort and confidence among nurses caring for older patients - Levkovich, Inbar (Palembang MediRose Publisher, 2023)
Human sexuality, a fundamental aspect of overall health and well-being, persists throughout all stages of the human lifecycle, including advanced age. Research demonstrates that a significant number of older adults maintain interest in sexual activity and continue to be sexually active during their later years. Nurses and healthcare providers must learn to understand the intricate interplay of psychological and physical influences leading to sexual difficulties among older individuals. Such knowledge is critical when providing effective assistance to older adults grappling with sexuality-related concerns. Given that the over 65 population accesses healthcare services frequently, healthcare professionals serve as pivotal intermediaries in addressing sexual issues. Nevertheless, medical personnel often feel uncomfortable and unsure about initiating conversations about sexuality among this population. This paper explores the reasons underlying the common tendency among healthcare professionals to avoid such discussions and suggests strategies to ameliorate this situation.